Birokrasi dan Politik Kekerabatan Pada Pemilu Legislatif 2024 Di Kabupaten Bangka Selatan - Putri, Putri; Ibrahim, Ibrahim; Hidayat, Novendra (Asosiasi Ide Bahasa Kepri, 2024)
Politics and bureaucracy are inseparable and interrelated. In the 2024 elections, especially in the legislative elections, bureaucracy is intertwined in kinship political relations. Bureaucracy and kinship politics refer to the practice where candidates or political parties use family relationships and the power they have within the bureaucracy to gain support and attempt to win elections. This research aims to identify related forms of utilization of bureaucratic resource-based kinship politics in legislative elections in South Bangka Regency. The theories used in this research are kinship theory by Schneider (1968) and resource mobilization theory by Oberschall (1973). This research uses a qualitative method with a descriptive approach where primary data sources are obtained through interviews, observation and documentation, while secondary data is obtained through library materials that can support primary information. The results of this research indicate that this form of utilization of bureaucratic resource-based kinship politics has a significant influence in determining a person's political choices and support. This can be seen from the family support provided through resource mobilization. The determinant factors for the emergence and success of this resource mobilization theory consist of five things including social organizational movements, leaders and leadership, resources and resource mobilization which are classified into five types, namely moral resources, cultural resources, social-organizational resources, human resources and material resources, then networks and participation, as well as opportunities and community capacity. In efforts to provide voting support to their families, bureaucratic actors are limited by regulations and public positions so that mobilization is not carried out optimally.